The influence of orifice height on flow rate of powder excipients - Zatloukal, Z; Sklubalová, Z (Die Pharmazie, 2011)
The influence of the orifice height of a cylindrical, flat-bottomed hopper on the mass flow rate of the free-flowable size fractions of sodium chloride and boric acid was investigated. It was observed that a zone of sudden acceleration of the mass flow under gravity occurred when a critical orifice height had been achieved. Based on the results, an orifice diameter equal to 12 mm with a height of between 8-16 mm is recommended for the faster flow of sodium chloride while an orifice diameter equal to 8 mm with a height of less than 8mm is appropriate for the slower flow of boric acid. In summary, the orifice height should be taken into consideration as an important parameter of a cylindrical test hopper in order to obtain a reproducible and comparable mass flow as the single-point characteristic of powder flowability.
Keywords: vlhkost; Temperature; pomocné látky; chlorid sodný; teplota; Excipients; vibrace; velikost částic; reprodukovatelnost výsledků; kyseliny borité; Reproducibility of Results; Humidity; Vibration; Powders; Technology, Pharmaceutical; Sodium Chloride; farmaceutická technologie; prášky, zásypy, pudry; Particle Size; Boric Acids